The effect of spray cycles on the morphological, structural, and optical properties of rGO thin film deposited using spray pyrolysis technique. (1st June 2021) - AlShammari, A.S.; Halim, M.M.; Yam, F.K.; Chahrour, K.M.; Raypah, M.E.; Kaus, N.H.M.
Abstract: This study proposed a facile and cost-effective approach to synthesize reduced graphene oxide (rGO) thin film from graphene oxide (GO) water dispersion. The rGO thin films were deposited on glass substrates via spray pyrolysis technique (SPT) by using different numbers of spray cycles (i.e. 2 to 10). The structure, morphology, thickness, and optical properties of GO and rGO thin films were characterized using different techniques. The optical analysis showed that the energy band gap of GO and rGO thin films reduced from 4.2 to 3.27 eV as the spray cycles were increased from 2 to 10, which confirms the effect of surface coating thickness on conductivity. To test the performance of the rGO thin film as a UV photodetector device, metal-semiconductor-metal (MSM) configuration was achieved by incorporating Al metal using RF sputtering on the thin film sample prepared with 10 spray cycles. For the device, the photoresponse ( R ) were found to be 0.0038, 0.0084, 0.01700, and 0.0284 (A/W), while photodetector gain ( G ) values were 1.956, 2.05, 2.15, and 2.31 at bias voltages of 1, 2, 3, and 4 V, respectively. At the same range of bias voltages, the rise times of the photodetector were 0.08, 0.075, 0.055, and 0.055 s, while the fall time were 0.055, 0.066, 0.06 and 0.06 s, respectively, under 375 nm UV illumination (0.37 mW/cm 2 ). The maximum sensitivity ( S %) was found to be 131.84 at 4 V. The photoelectric properties and photodetection performances indicate that rGO thin film deposited on glass substrate by SPT could be a potential candidate for the development of advanced MSM optoelectronic devices.